Penerapan Strategi Kompensasi pada Stasiun Meteorologi Kelas I Hang Nadim Batam - Rina Rahmawati; Adi Irawan Soetyanto (Politeknik Negeri Batam, 2015)
This final project aims to apprehend the application of compensation strategies at Batam Hang Nadim Meteorological Stasion Class 1 that leads to achieve internal alignment. This is a qualitative descriptive analysis type of study. The data collection used in this final project were by interviews, observation and documentation techniques. This results that ratio comparison average of basic salary is 1:1,3, the remuneration shared by the amount of Rp2.010.000,- is out of transparency calculation, and work attendance is the significant value of calculating incentives pay. The researcher suggests that company gets to support non-financial needs of employees, increase transparency in policy regarding to payroll issues, and provide incentives based on performance related pay.